Voices of crime: constructing and contesting social control in modern Latin America - Huertas Castillo, Luz; Lucero, Bonnie A.; Swedberg, Gregory J.; Swedberg, Gregroy J.; Salvatore, Ricardo Donato (The University of Arizona Press, 2016)
"The book is a collection of essays looking at histories of crime and justice in Latin America, with a focus on social history and the interactions between state institutions, the press, and social groups. It argues that crime in Latin America is best understood from the "bottom up" -- not just as the exercise of power from the state. The book seeks to document and illustrate the "every day" experiences of crime in particular settings, emphasizing under-researched historical actors such as criminals, victims, and police officers"--Provided by publisher